1987
DOI: 10.1111/j.1471-4159.1987.tb05642.x
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Nucleotide and Cation Regulation of μ, δ, and k Opioid Receptor Binding: Evidence for Differential Postnatal Development in Rat Brain

Abstract: A study of the onset of cation and guanine nucleotide regulation of delta, mu, and kappa rat brain opioid receptors during postnatal development was undertaken. Site-specific binding assays were utilized for each receptor type and the effects of 0.5 mM MnCl2, 100 mM NaCl, and/or 50 microM guanosine-5'-(beta, gamma-imido) triphosphate [Gpp(NH)p] were assessed. The most pronounced changes of opioid binding were seen in the presence of Mn2+. In adults, agonist binding to delta sites was stimulated by Mn2+, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Gpp(NH)p inhibited opioid agonist binding in SPM preparations similar to unfractionated membranes (Szucs et al, 1987, and references therein), whereas microsomes were relatively insensitive (Figs. l and 2).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Gpp(NH)p inhibited opioid agonist binding in SPM preparations similar to unfractionated membranes (Szucs et al, 1987, and references therein), whereas microsomes were relatively insensitive (Figs. l and 2).…”
Section: Resultsmentioning
confidence: 94%
“…1 . Modulation of p , 6, and K opioid receptor binding in SPM and microsomes by 50 pM Gpp(NH)p (G), 100 mM NaCl (Na), and/or 0.5 mM MnCI, (Mn (Szucs et al, 1987). Where appropriate, membranes (== 1 mg protein) in a Tris buffer containing protease inhibitors were treated with 1 % digitonin at 4°C for 30 min, then centrifuged at 100,OOOg for 1 hr to yield a solubilized preparation as described elsewhere (Simon et al, 1986).…”
Section: Binding Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the early opioid literature showed that δ‐receptors were regulated by guanine nucleotides and Na + (Blume, 1978; Pert & Snyder, 1974; Pfeiffer et al , 1982; Werling et al , 1984; Zajac & Roques, 1985) and that the loss of binding of agonist but not antagonists probably reflected uncoupling of the G‐protein from its receptor (Childers, 1991). Although the extent of the reduction of agonist binding for both GTP analogues and Na + varies (Chang et al , 1983; Puttfarken et al , 1986; Szucs et al , 1987) these differences have often been suggested to reflect differences in the experimental systems (Cox, 1993).…”
Section: Discussionmentioning
confidence: 99%